The Effect of some Variables on the Formulation of Captopril as Tablets Shaymaa Nazar Al – Sammarrai - A. Abdul R asool, Dr. Alaa; Al – Dujali, Dr. Hikmet (Iraqi Journal of Pharmaceutical Sciences, 2017)
Captopril is an angiotensin converting enzyme inhibitor (ACEI) used to treat hypertension,congestive heart failure, and myocardial infraction.The only dosage form available for captopril is the plain tablet in strength of 12.5,25,50 and 100mgtablet.This investigation is concerned with factors affecting the formulation of captopril as a plaintablet dosage form of 50mg. Many trials were made to prepare satisfactory tablets for the drug byusing wet – granulation methods with various additives. It was found that poly vinyl pyrrolidone(P.V.P.) as binder gave the most satisfactory tablets. At the same time a shorter disintegrantion timeand slower dissolution rate were obtained with the addition of starch intragranular.While the distintegration time and dissolution rate were faster for explotab when it was usedintragranular in comparison with starch.A comparative study on the physical properties of the prepared tablets with Capoten®(Squibb), Miniten® (APM), and Capocard® (DAD) tablets, showed that the release of drug from theselected formula was similar to that obtained from Miniten® at 0.1N HCl and 37C.The stability of the prepared tablet was also studied at 50C, 60C, and 70C for 4 months andthe calculated shelf – life was about 3.5years at 25C.